Current-Loading Capacity Investigations of Current Collector Operated with Mainline Electric Motive Power - V. M. Pavlov; O. A. Sidorov; A. N. Smerdin; V. V. Tomilov; A. S. Golubkov; D. V. Tartynskiy (Вестник Научно-исследовательского института железнодорожного транспорта)
To implement specified motion modes modern high-speed electric locomotives must be high-powered enough with hourly and continuous rating up to 10,000 kW. At 3,300 V DC electrified lines this requires current collection in excess of 3,000 A. International and domestic practices indicate that at high speed levels current pick-up worsens proportionally to the number of current collectors engaged in the interaction with contact wire. Also due to the lack of space it is rather difficult to have more than two current collectors on the roof of a modern single-unit dual-system electric locomotive. Advanced contact strip materials allow for 3,200 A continuous pick-up in motion with a single current collector. The paper contains experimental investigations’ outcomes of the PanTrac contact elements. Those investigations conducted on the task-specific rig in the OmGUPS’s laboratory facility demonstrated that wide use of such contact strips on heavy- traffic railway lines could bring long-term benefits. There are described checking procedures allowing to observe the required conditions and existing allowances.